Pengukuran resapan air ke dalam konkrit dengan menggunakan kaedah ujikaji Resapan awalan permukaan - Mohd Sabri Abdullah ,; Kamarudin Mohd Yusof, (1990)

(untitled)
Water absorption into concrete was measured by ISAT method. Concrete samples with different aggregate size, duration of moistcuring and water-cement ratio were tested. The results showed that by decreasing the duration of moistcuring and watercement ratio, the water absorption decreases, but the increase of the aggregate size will decrease the rate of absorption